Nexus between idiosyncratic deals and work engagement via psychological empowerment: A PLS-SEM approach - Muhammad Shahid Shams, Tang Swee Mei, Zurina Adnan (Management Science Letters, 2020)
Idiosyncratic deals have been used by many organizations to achieve desirable employees’ behavior and work-related positive outcomes. Drawing upon the social exchange theory, this study aims at investigating the connections between idiosyncratic deals and work engagement. Besides, this study also scrutinizes the mediating role of psychological empowerment in the relationship between idiosyncratic deals and work engagement. This study applied smart PLS-SEM v.3.2 for the data analysis to ascertain the relationship between the study variables. Using an online survey, data are collected from 310 academicians working in the public higher education institutions of Pakistan. The finding of this study shows a significant positive relationship between idiosyncratic deals and work engagement. Furthermore, finding of the study also divulges that psychological empowerment mediates the relationship between idiosyncratic deals and work engagement. Hence the management and the policy makers in the public higher education institutions should focus on the provision of idiosyncratic deals based on the personal and professional needs of academicians to strengthen their feeling of psychological empowerment which subsequently results in fostering their engagement at work.